Did healthy life awareness affect the behavioral or cognitive avoidance attitude from COVID-19? An observational study - Ayşegül Şen; Melike Mercan Başpınar; Okcan Basat (Journal of Family Medicine and Primary Care)
Aim: This study purposed to evaluate the healthy life awareness (HLA) level versus the COVID-19 avoidance attitudes. Materials and Methods: A single-centered observational study was conducted in the Family Medicine Clinics of a tertiary hospital between April 30, 2021 and July 30, 2021. The HLA scale was used to determine the participants' HLA levels. In addition, the avoidance attitudes from the COVID-19 scale score assessed attitudes toward avoiding COVID-19. Data were analyzed with E-Picos (MediCRES) Statistical Programme. Results: Of the 311 participants aged 30.79 ± 8.37 years, 58.52% (n = 182) were female and 41.48% (n = 129) were male. A negative relationship between the HLA and cognitive avoidance scores (r = −0.255, P < 0.001) and a positive relationship between HLA and behavioral avoidance scores (r = 0.119, P = 0.036) have been indicated. The results of a binary logistic regression, taking the presence of a higher HLA score as the dependent variable, have shown that high awareness was observed in women, approximately 1.7 times more than in men [odds ratio (OR): 1.684, 95% confidence interval (CI) = 1.058–2.696; P = 0.030]. Participants with high HLA had 1.06 times higher behavioral avoidance scores than others (OR: 1.066, 95% CI = 1.012–1.455; P = 0.049). As the cognitive avoidance score increased, the presence of high HLA decreased by nearly 33%. (OR: 0.666, 95% CI = 0.512–0.867; P = 0.002). Conclusion: This study emphasized that a higher HLA was associated with increased behavioral avoidance and decreased cognitive avoidance from COVID-19. HLA has led to doing what needed to be done without being affected by negative discourses.